The Relationship Between Perfectionism and Sports Ethics Among Young Athletes Based on Achievement Goal Theory - Sun, Kaihong; Ji, Tai (Frontiers in Psychology, 2022)
Exercise plays an important role in the process of socialization among young people and children by providing a context in which children can be exposed to the existing rules and values of society. However, the increasing news of unethical behaviors reported in competitive scenarios led the public to suspect the view "Sports shapes great characters". In order to investigate the issue and explore potential influencing factors, the study examined the relationship between athletes’ perfectionism, achievement goals, and sports ethics based on the Achievement Goal theory. A total of 243 young athletes were recruited. The multidimensional perfectionism, achievement goals and sports ethics were measured by a battery of questionnaires. A direct effect model that did not include mediation variables (achievement goals) and a mediation effect model that included mediation variables were analyzed by structural equation modeling (SEM). Results indicated that perfectionistic strivings may positively predict sports ethics, while perfectionistic concerns may negatively predict sports ethics. Mastery-approach and mastery-avoidance may positively predict sports ethic, while the performance-approach and performance-avoidance may negatively predict sports ethic. Achievement goal may partially mediate the relationship between perfectionism and sports ethics. Perfectionistic strivings may negatively predict sports ethics through performance-approach and positively predict sports ethics through mastery-approach. perfectionistic concerns may negatively predict sports ethics through performance-avoidance and positively predict sports ethics by mastery-avoidance. In order to prevent athletes from using unethical behaviors, strategies should be developed to reduce perfectionistic concerns and increase their perfectionistic strivings.